Synthesis of redox-active fluorinated 5-hydroxytryptophans as molecular reporters for biological electron transfer. Issue 25 (24th February 2021) - Ohler, Amanda; Long, Hanna; Ohgo, Kei; Tyson, Kristin; Murray, David; Davis, Amanda; Whittington, Chris; Hvastkovs, Eli G.; Duffy, Liam; Haddy, Alice; Sargent, Andrew L.; Allen, William E.; et al.
Abstract : Chemoenzymatic synthesis of fluorinated 5-hydroxytryptophans provides a novel set of non-canonical tryptophan amino acids useful for probes of biological electron transfer reactions. Abstract : Fluorinated 5-hydroxytryptophans (F n -5HOWs) were synthesized in gram scale quantities and incorporated into a β-hairpin peptide and the protein azurin. The redox-active F n -5HOWs exhibit unique radical spectroscopic signatures that expand the function of ; 5HOW as probes for biological electron transfer.